Psychological, covid-19 and co-ass students - Sri P. Utami; Fadhlurrahman (DiscoverSys Inc., 2021)
Objective: The purpose is To find out the psychological impact of the COVID-19 epidemic on the class 2019 co-ass students of the Faculty of Dentistry Baiturrahmah University.Material and Methods: This type of research is descriptive research. The target population of this study were co-ass students of class 2019, with a sample of 142 people. This research was conducted online in the city of Padang using google form media for distributing questionnaires. When the research was carried out in October 2020. The 7-item General Anxiety Disorders Scale (GAD-7) is the most widely used instrument for detecting and screening anxiety disorders, and is a module of the Patient Health Questionnaire. Sa total of 52.8% of respondents disclosed that their family income was unstable and 47.2% was stable.Results: that there were 5.6% feeling normal, 36.6% moderate and 57.7% severe. In addition, relatives or acquaintances affected by Covid-19 are around 2.8%.Conclusion: The data analysis method in this study used the SPSS program with univariate and bivariate analysis. Processed data is presented in tabular form and in percentage form